1978
DOI: 10.1172/jci109147
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Alpha Adrenergic Blockade upon Coronary Hemodynamics

Abstract: A B S T R A C T The effect of alpha adrenergic blockade on coronary blood flow regulation at rest was studied in 11 normally innervated patients and 8 cardiac allograft recipients by measuring arterial pressure and coronary sinus blood flow by thermodilution before and after alpha adrenergic blockade with phentolamine. Coronary vascular resistance was calculated by using coronary sinus blood flow and mean arterial pressure, and metabolic demand was estimated by the product of systolic arterial pressure and hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
10
0

Year Published

1980
1980
2004
2004

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(13 citation statements)
references
References 36 publications
3
10
0
Order By: Relevance
“…The impact of alpha adrenergic activity on coronary vascular resistance has been demonstrated in experimental myocardial infarction (47)(48)(49) and recently in a clinical study. In patients with stable ischemic heart disease, increase in coronary vascular resistance and chest pain, provoked by cold pressure test, were abolished by alpha adrenergic blockade (50).…”
Section: Methodsmentioning
confidence: 97%
“…The impact of alpha adrenergic activity on coronary vascular resistance has been demonstrated in experimental myocardial infarction (47)(48)(49) and recently in a clinical study. In patients with stable ischemic heart disease, increase in coronary vascular resistance and chest pain, provoked by cold pressure test, were abolished by alpha adrenergic blockade (50).…”
Section: Methodsmentioning
confidence: 97%
“…52, No. 1, January 1983 benzamine (Mohrman and Feigl, 1978;Orlick et al, 1978;Murray and Vatner, 1979;Gwirtz and Stone, 1981;Heyndrickx et al, 1982). Even in left circumflex artery where postjunctional a-adrenergic responses occur, the prejunctional action of phentolamine during low frequency stimulation may be solely responsible for the augmented relaxation of coronary vascular smooth muscle observed in the presence of the a-adrenergic antagonist.…”
Section: Prejunctional Actions Of Endogenous Norepinephrinementioning
confidence: 99%
“…/8-Adrenergic coronary vasodilation accompanies sympathetic activation resulting from hypothalamic stimulation in conscious dogs (Von Restorff and Bassenge, 1976), but the prevailing opinion is that cardiac sympathetic nerves exert a tonic a-adrenergic constrictor influence on coronary resistance which persists even during severe exercise (Berne et al, 1965;Feigel, 1968;Vatner et al, 1970;Mohrman and Feigl, 1978;Orlick et al, 1978;Berne and Rubio, 1979;Murray and Vatner, 1979;Gwirtz and Stone, 1981;Heyndrickx et al, 1982). This conclusion is based largely on the characterization of coronary vascular responses using nonselective a-adrenergic antagonists (e.g., phentolamine or phenoxybenzamine) which, by augmenting norepinephrine release (Stjarne, 1975;Starke and Docherty, 1980;Langer, 1981), could significantly alter the response to nerve stimulation.…”
mentioning
confidence: 99%
“…7 8 The mechanism of such variation in coronary artery vasomotion is unknown, but several studies have implicated a central role for the adrenergic nervous system. [9][10][11][12][13][14][15][16] Studies in animals have shown that coronary artery vasoconstriction and increases in coronary vascular resistance can be elicited by sympathetic stimulation after 13-adrenergic blockade. '2'2 1'1 Clinical studies of patients with variant angina have shown exacerbation of coronary spasm after subcutaneous administration of epinephrine in patients receiving propranolol.…”
mentioning
confidence: 99%